Review of studies on ammonia recovery via struvite precipitation - Rodrigues, Letícia Mothé do Nascimento; Bazoni, Raniella Falchetto; Cotta, Aloísio Jo´sé Bueno (Brazilian Journal of Production Engineering, 2021)
The precipitation of struvite (MgNH4PO4.6H2O), integrated with the treatment of effluents, is environmentally and economically attractive. In this review, the most cited publications (of the past 20 years) dedicated to recovering nutrients from effluents via struvite precipitation were identified. The operating conditions (pH, the proportion of reagents, reaction time and agitation conditions, and raw materials used) and results achieved were examined, aiming to identify the factors controlling the nutrient recovery process's efficiency. To this end, a review was carried out on the Web of Science database, with the terms (struvite, ammonium, recovery, nutrient, treatment) to select the articles. The relevance and timeliness of the theme were noticed by many recent publications. In general, the best results were obtained with pH 8.5-9.0 and a slight excess of Mg2+, from magnesia (industrial MgO). Which, in addition to increasing the yield, reduces the cost of the process. In contrast to the tests with synthetic effluents, studies with real effluents highlight that the presence of K+ (Ca2+ and HCO3-) must be considered when adjusting the added quantities of reagents. Virtually all studies reported that ammonia recovery is more difficult and occurs in lower percentages than P. It is noteworthy that the agronomic evaluation of the struvite obtained revealed its great applicability as a slow-release fertilizer, which financially enables the nutrient recycling process.
Keywords: Struvite; wastewater treatment; review